Adaptation of the Arabic Version of the Tinnitus Handicap Inventory. (March 2016) - Barake, Rana; Rizk, Samer Abou; Ziade, Georges; Zaytoun, George; Bassim, Marc
Objective: To translate the Tinnitus Handicap Inventory (THI) into literary Arabic to come up with a unified Arabic version and to determine its validity and reliability in assessing the quality of life of Arabic-speaking patients with tinnitus. Study Design: Clinical measurement study. Setting: Tertiary care center. Subjects and methods: The original English THI was translated into literary Arabic by a forward- and back-translation process according to the published guidelines for cross-cultural adaptation of health-related quality-of-life measures and applied to 100 patients with chronic tinnitus. Internal consistency reliability was then assessed by calculating Cronbach's alpha coefficient. Pearson correlation coefficients were also calculated for the different scales and the different baseline characteristics. Results: Results showed high internal consistency and reliability coefficients (total THI: 0.93, functional subscale: 0.86, emotional subscale: 0.86, catastrophic subscale: 0.66) comparable to those of the original English THI. Conclusion: The Arabic version of the THI is a valid and reliable tool for the assessment of the impact of tinnitus on the quality of life of Arabic-speaking patients with the complaint of chronic tinnitus.